1983
DOI: 10.1007/bf01960623
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia induced in mice by injection of venom sac extract of hornets (Vespa orientalis, Vespinae: Hymenoptera)

Abstract: Intraperitoneal injection into naive and immunized albino mice of Oriental hornet venom sac aqueous extract induces within 3 h an 8-10 degrees C and 3-4 degrees C drop in body temperature, respectively. The fall in temperature is dose-dependent. The responsible fraction(s) in the venom is of high molecular weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As for the occurrence of hypothermia we demonstrated in a previous study that one fraction in hornet venom, namely mastoparan, is responsible for inducing hypothermia in mammals (Duvdevani et al 1991). In earlier studies we reported the induction by hornet venom of hypothermia in albino (ICR) mice (Ishay et al 1983) as well as in cats (Barenholz-Paniry et al. 1990).…”
Section: Discussionmentioning
confidence: 98%
“…As for the occurrence of hypothermia we demonstrated in a previous study that one fraction in hornet venom, namely mastoparan, is responsible for inducing hypothermia in mammals (Duvdevani et al 1991). In earlier studies we reported the induction by hornet venom of hypothermia in albino (ICR) mice (Ishay et al 1983) as well as in cats (Barenholz-Paniry et al. 1990).…”
Section: Discussionmentioning
confidence: 98%